Managerial risk-reducing incentives and social and exchange capital - Zhuang Zhang; Amon Chizema; Jing-Ming Kuo; Qingjing Zhang (2021)
This study investigates the impact of managerial risk-reducing incentives on the firm's social and exchange capital. Using CEO inside debt holdings to proxy for the incentives of risk-averse managers, we find that CEOs with more inside debt holdings are likely to invest more in building social capital, which targets broader society and potentially offers anti-risk protection advantages, to shield the value of their inside debt. However, our results further show that managerial risk-reducing incentives have no impact on firms' exchange capital, suggesting the need to recognize the difference between social and exchange capital. These findings corroborate the view that CEOs invest in social capital as a risk management strategy. Furthermore, this paper presents an understanding of the role that institutional investors play in moderating the impact of managerial risk-reducing incentives on social capital. Our results suggest that institutional investors constrain CEOs that have greater inside debt incentives from investing in social capital. However, they are still willing to increase the investment in social capital for risk management purposes when firm risk is high.